Afghanistan in Transition : Looking Beyond 2014 - World Bank (Washington, DC, 2017)
Afghanistan will experience a major security and development transition over the next three years. At the Kabul and Lisbon Conferences in 2010, NATO and the Afghan government agreed that full responsibility for security would be handed over to the Afghan National Security Forces (ANSF) by the end of 2014. Development progress since 2001 has been mixed. Some major achievements have been recorded, such as rapid economic growth (with large fluctuations), relatively low inflation (after hyperinflation in the 1990s), better public financial management, and gains in basic health and education. Key social indicators, including life expectancy and maternal mortality, have improved markedly (admittedly from an extremely low base), and women are participating more in the economy. Yet in other respects, particularly governance and institution building, the country has fared less well, and many indicators have worsened in recent years. Afghanistan remains one of the world's least developed countries, with a per capita gross domestic product (GDP) of only $528 in 2010/11. More than a third of the population live below the poverty line, more than half are vulnerable and at serious risk of falling into poverty, and three?quarters are illiterate. This report is intended to be comprehensive, so it also discusses the broader historical and political economy context of development in the country, and how Afghanistan compares with other countries that have undergone their own transitions over the past 30 years. This report is based on data collected from various sources in 2011, and its analysis and findings therefore comprise the team's considered assessment using the best available information available by the end of that year. In addition, projections of future trends in Afghanistan inevitably are subject to uncertainty and reflect any weaknesses in the underlying data. Thus the report's projections should be seen as subject to further adjustments and improvements as better and more recent information become available. This report is presented in two volumes. Volume one is a stand?alone Overview which highlights the main findings, projections, and recommendations of the study. Volume two consists of five chapters presenting the detailed empirical background, analytical findings, projections, and recommendations of the study, along with a concluding chapter and three technical appendices.